SUPPORTING SYSTEM OF FRAUD DETECTION ON FINANCIAL STATEMENTS - Gery Lisiano Firmansah; Nurul Fitriani (Fakultas Bisnis UKDW, 2020)
ABSTRACT The use of audit activities is to ensure that the financial statements are free from material misstatement as a basis for making decisions by users of financial statements. In its activities, auditors often fail to detect fraud or errors committed by the company. Currently, systems and digitization are developing in a business environment that is so fast, and helps process complex and dynamic information and data. This study aims to help auditors build a system in the process of detecting fraud in a company's financial statements. The system used here involves the participation of Big Data in issues related to volatility, uncertainty, complexity, and ambiguity, and involves a Learning System with the accuracy of detecting fraud in financial reports. This research is designed to reduce losses and the risk of failed audits by auditors, risks in decision making by investors and creditors. This research will form a Supporting System in the form of a fraud detection system design, development until the accuracy results are achieved.Keywords: System, Learning, Big Data, Fraud Detection, Financial StatementABSTRAKKegunaan kegiatan audit adalah memastikan bahwa laporan keuangan telah bebas dari salah saji yang material sebagai landasan dalam pengambilan keputusan oleh pengguna laporan keuangan. Dalam kegiatannya, auditor sering kali gagal untuk mendeteksi adanya fraud maupun error yang dilakukan oleh perusahaan. Saat ini, system dan digitalisasi berkembang dalam lingkungan bisnis yang begitu cepat, dan membantu pengolahan informasi dan data yang kompleks serta dinamis. Penelitian ini bertujuan untuk membantu auditor membangun sistem dalam proses pendeteksian kecurangan dalam laporan keuangan perusahaan. System yang digunakan disini melibatkan peran serta Big Data dalam permasalahan yang berkaitan dengan volatility, uncertainty, complexity, and ambiguity, serta melibatkan Learning System dengan akurasi pendeteksian kecurangan dalam laporan keuangan. Penelitian ini dirancang untuk mengurangi kerugian dan risiko gagal audit oleh auditor, risiko dalam pengambilan keputusan oleh investor dan kreditor. Penelitian ini akan membentuk sebuah Supporting System berupa desain system deteksi kecurangan, pengembangan hingga hasil akurasi yang dicapai.Kata Kunci: .Sistem, Pembelajaran, Big Data, Deteksi Penipuan, Laporan Keuangan